DISTANCE TO HEALTH FACILITIES WITH LOW DELIVERY ASSISTANCE BY HEALTH PERSONNEL IN THE WORKING AREA OF BIBIDA HEALTH CENTER PANIAI DISTRICT CENTRAL PAPUA - sari, silvie pertama (E-Jurnal Medika Udayana; Vol 13 No 4 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i04.P08, 2024)
Maternal and newborn complications and deaths mostly occur in the period around childbirth. This is partly because help is not provided by health workers who have midwifery competence. In 2021, 56.3% of births were assisted by health workers in Papua Province. At the Bibida Community Health Center, 32% of births were assisted by health workers. The aim of this research is to examine the relationship between the distance to health facilities and the low level of birth assistance by health workers in the Bibida Health Center working area. The type of research used is quantitative, employing a descriptive design with a cross-sectional approach. This research was conducted from October 2023 to November 2023 in the Bibida Health Center working area, Paniai Regency, Central Papua. The population in this study consisted of all postpartum mothers in the Bibida Community Health Center working area in July, August, and September. Samples were selected using a total population technique, resulting in 35 samples. Computerized univariate and bivariate data processing was conducted using the chi-square statistical test. The research findings showed that the percentage of births assisted by non-health workers was 62.9%, while the percentage of births in relation to the distance to health facilities was 54.3%. The statistical analysis results indicated a significant relationship between the distance to health facilities (p-value = 0.000) and the level of birth assistance by health workers.